Andrew Lloyd Webber's love never dies [videorecording (DVD)] - Lloyd Webber, Andrew, 1948- (Universal Studios Home Entertainment, 2012)
The year is 1907. It is ten years after the Phantom's disappearance from the Paris Opera House. He has escaped to a new life in New York, where he lives among the screaming joy rides and freak-shows of Coney Island. In this new electrically charged world, he has finally found a place for his music to soar. All that is missing is his love - Christine Daae. Now one of the world's finest sopranos, Christine is struggling in an ailing marriage to Raoul.